Correction: Copper(ii) gluconate (a non-toxic food supplement/dietary aid) as a precursor catalyst for effective photo-induced living radical polymerisation of acrylates. Issue 47 (28th November 2017) - Nikolaou, Vasiliki; Anastasaki, Athina; Alsubaie, Fehaid; Simula, Alexandre; Fox, David J.; Haddleton, David M.
Abstract : Correction for 'Copper(ii ) gluconate (a non-toxic food supplement/dietary aid) as a precursor catalyst for effective photo-induced living radical polymerisation of acrylates' by Vasiliki Nikolaou et al., Polym. Chem., 2015, 6, 3581–3585.